Improving Gene Editing Outcomes in Human Hematopoietic Stem and Progenitor Cells by Temporal Control of DNA Repair. (27th November 2018) - Lomova, Anastasia; Clark, Danielle N.; Campo-Fernandez, Beatriz; Flores-Bjurström, Carmen; Kaufman, Michael L.; Fitz-Gibbon, Sorel; Wang, Xiaoyan; Miyahira, Eric Y.; Brown, Devin; DeWitt, Mark A.; Corn, Jacob E.; Hollis, Roger P.; et al.
Abstract : Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated system (Cas9)-mediated gene editing of human hematopoietic stem cells (hHSCs) is a promising strategy for the treatment of genetic blood diseases through site-specific correction of identified causal mutations. However, clinical translation is hindered by low ratio of precise gene modification using the corrective donor template (homology-directed repair, HDR) to gene disruption (nonhomologous end joining, NHEJ) in hHSCs. By using a modified version of Cas9 with reduced nuclease activity in G1 phase of cell cycle when HDR cannot occur, and transiently increasing the proportion of cells in HDR-preferred phases (S/G2), we achieved a four-fold improvement in HDR/NHEJ ratio over the control condition in vitro, and a significant improvement after xenotransplantation of edited hHSCs into immunodeficient mice. This strategy for improving gene editing outcomes in hHSCs has important implications for the field of gene therapy, and can be applied to diseases where increased HDR/NHEJ ratio is critical for therapeutic success. Stem Cells   2019;37:284–294 : Abstract : A modified version of Cas9 (hGemCas9) with reduced nuclease activity in G1 phase of cell cycle, when homology-directed repair cannot occur, and transient synchronization of mobilized peripheral blood stem cells in homology-directed repair-preferred phases (S/G2) resulted in a four-fold improvement in the ratio of homology-directed repair to nonhomologous end joining over the control condition in vitro, and a significant improvement after xenotransplantation of edited human hematopoietic stem cells into immunodeficient mice.